Temporal dynamics of litter quality, soil properties and microbial strategies as main drivers of the priming effect - Fanin, Nicolas; Alavoine, Gonzague; Bertrand, Isabelle (Geoderma, 2020)
•Addition of high quality litter generates an ‘immediate’ priming effect.•Addition of low quality litter generates a ‘delayed’ priming effect.•Carbon incorportion in soil couterbalances carbon loss by priming effect. The priming effect describes the change in the rate of soil organic matter (SOM) mineralisation due to the addition of fresh organic matter (FOM), and is thus central to the evaluation of carbon fluxes in terrestrial ecosystems. However, little is known about how litter quality interact with soil properties and microbial communities to explain the priming effect. Here, we provide new empirical evidence showing how litter, soil and microbial parameters control FOM and SOM decomposition. We monitored the kinetics of carbon fluxes over 202 days and at 23 dates after additions of two 13C-labelled plant litters of contrasted quality (nutrient-rich and labile litter [i.e., high quality] vs nutrient-poor and recalcitrant litter [i.e., low quality]) using four soil types originating from different ecosystems (forest, grassland, cropland and plantation). We found that the priming effect varied over time with: (i) an ‘immediate’ priming effect after the addition of high quality litter, which rapidly decreases when nitrogen is available; and (ii) a ‘delayed’ priming effect after the addition of low quality litter, which increases continuously when nitrogen is depleted. The ‘immediate’ priming was mainly related to the decomposition of accessible carbon compounds, whereas the ‘delayed priming’ was mainly related to the decomposition of recalcitrant carbon compounds. These results were linked to changes in microbial resource acquisition strategies as indicated by shifts in enzyme activities from hydrolytic to oxidative and nitrogen-related enzymes, therefore suggesting that two series of mechanisms act in succession at different time scales in relation to litter quality and nitrogen availability. Furthermore, our data demonstrate that incorporating carbon in the soil via the increase in soil microbial biomass can counterbalance carbon losses via priming effect. This highlights the importance to assess the balance between the carbon outputs and inputs to determine whether terrestrial ecosystems act as a sink or a source of carbon. We conclude that shifts in litter quality, nutrient availability and microbial resource acquisition strategies need to be taken into consideration for accurate assessment of the variability of the priming effect from the short to the long term.